Educational assessment of diabetics requiring vascular surgery - Hlinková, Edita; Nemcová, Jana; Žiaková, Katarína (Central European Journal of Nursing and Midwifery, 2017)
Aim: Educational assessment involving epistemological, axiological, and technical conditions was demonstrated to be an important part of the educational process of improving the knowledge and behavior of diabetics requiring vascular surgery. Design:A quantitative interventional prospective study. Methods:The theoretical model of Practical Reasoning of Humanistic Interpretation Method was used to construct the educational assessment. The assessment was followed up by a quantitative interventional prospective study to determine conditions of behavior before and after education. The research sample comprised of diabetics with diabetic foot syndrome (DFS) (n = 52), and with Low Extremities Arterial Disease (LEAD) (n = 48) from the University Hospital in Martin, Slovakia. Results: We found no differences in epistemological, axiological, and technical conditions of diabetics with DFS versus LEAD before education. Six months after education, we found significantly better knowledge in patients with DFS. Group education methods, family status, and membership of a diabetics’club were some of the educational assessment factors confirmed as significant following education of both groups. Conclusion: Educational assessment based on a theoretical model of practical reasoning and behavior revealed a number of differences and conditions which determined learning and behavior in the case of vascular surgery patients, and, we may assume, others besides.
Keywords: znalosti; diabetická noha; Male; emoce; Slovakia; rozhovory jako téma; Interviews as Topic; Slovenská republika; Thinking; nemoci cév; statistika jako téma; Emotions; myšlení; Diabetes Mellitus, Type 2; Prospective Studies; Motivation; mužské pohlaví; senioři; Diabetic Foot; Aged; Vascular Diseases; diabetes mellitus 2. typu; Patient Education as Topic; vzdělávání pacientů jako téma; Theoretical model of Practical Reasoning of Humanistic Interpretation Method; lidé; motivace; ženské pohlaví; Humans; Knowledge; Female; Statistics as Topic; lidé středního věku; Middle Aged; prospektivní studie